Analisis Kinerja Keuangan dan Pertumbuhan Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Tahun 2019 - 2021) - Adjie, Hendra Cahyo; Indriani, Eni; Mariadi, Yusli (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to examine the financial performance and profit growth of manufacturing companies listed on the Indonesia Stock Exchange (years 2019 – 2021). This study was conducted using an associative quantitative approach on 129 manufacturing companies listed on the Indonesia Stock Exchange for the years 2019 - 2021. The method used in the data analysis process involved the assistance of SmartPLS 4 software. The results of this study indicate that the current ratio, debt to equity, and return on assets are negative and do not have a significant effect on profit growth in manufacturing companies. The conclusion of this research reveals that the influence of the current ratio, debt to equity, and return on assets on profit growth from 2019 to 2021 is not significant and does not affect profit growth; thus, the hypothesis that an increase in the current ratio, debt to equity ratio, and return on assets will impact the development of these companies is incorrect. This finding is very useful for financial statement users in assessing and making decisions